Organizational Identity for Cross-border Digital Trade: Achieving Technical and Legal Interoperability Within the Model Law on the Use and Cross-border Recognition of Identity Management and Trust Services (MLIT) Using the vLEI - Marin, Ivan; Castellani, Luca G. (UNNExT Working Paper, 2025)
Identity management is a cornerstone of digital trade and a core component of trust services, starting with electronic signatures. However, there is limited awareness of its legal and technical implications. The United Nations Commission on International Trade Law (UNCITRAL) has prepared a Model Law on the Use and Cross-border Recognition of Identity Management and Trust Services to provide uniform guidance on how to establish an enabling legal environment for identity management and trust services. The Global Legal Entity Identifier Foundation (GLEIF) has developed the Legal Entity Identifier (LEI) and its digital counterpart the verifiable LEI (vLEI) as universal solutions for a secure and cost-effective persistent business identifier. This paper illustrates how the MLIT and the vLEI may interact to provide legal and operational certainty to identification needs, thus fostering global economic growth.
Keywords: Digital cross-border trade; Digital trade; GLEIF; LEI; Legal entity digital identity; MLTR compliance; Trade facilitation; vLEI verifiable credential

Legal remedies for breach of E-commerce contracts and related offences in Cameroon: a critical analysis - Saidou, Dan Lamy Nouhou (International Multilingual Journal of Science and Technology, 2025)
Avec de plus en plus de transactions commerciales effectuées par voie électronique, les litiges résultant d'intérêts conflictuels ou de malveillance deviennent inévitables, car Internet est devenu un terreau fertile pour divers abus. Ces abus vont de la rupture de contrat et des actes délictuels aux actes criminels. Il en résulte que l'utilisation d'Internet a donné une dimension différente à ces litiges. Cependant, comme le dit la célèbre maxime Ubi Jus Ubi Remedium, là où il y a un droit, il y a un remède. Le Cameroun, suivant cette tendance, a adopté un cadre juridique qui offre une panoplie de recours disponibles pour les victimes de violations du commerce électronique et d'infractions connexes, dans l'intention de rapprocher la partie lésée le plus possible de la position qu'elle aurait occupée s'il n'y avait pas eu d'abus. Le but de cet article est d'évaluer l'efficacité du cadre actuel pour remédier aux victimes de violations du commerce électronique et d'infractions connexes. L'article examine donc les bases des responsabilités en commerce électronique et les recours disponibles pour les victimes, mettant en évidence les difficultés qui rendent ces recours moins efficaces à cet égard. Plusieurs recommandations ont été proposées par cet article pour améliorer le statu quo. With more and more business being conducted through electronic means, disputes stemming from conflicting interests or malice become inevitable, as the internet has become a breeding ground for diverse abuses. These abuses range from contractual breaches and tortious acts to criminal acts. It follows that the use of the internet has given a different dimension to these disputes. However, as the famous maxim Ubi Jus, Ubi Remedium states, where there is a right, there is a remedy. Cameroon, following this trend, adopted a legal framework that provided a panoply of remedies available to victims of breaches of e-commerce contracts and related offenses to bring the aggrieved party as close as possible to the position he would have been in if there had been no abuse. The purpose of this article is to assess the efficiency of the present framework for remedying victims of e-commerce breaches and related offenses. The article thus examines the basis for liabilities in e-commerce and the remedies available to victims, bringing out the difficulties which render these remedies less efficient for the purpose. Several recommendations have been proffer by this article to improve the status quo.
Keywords: Commerce électronique; E-commerce; Electronic transactions; Recours; Remedies; Transactions électroniques

Implementation of safeguard measures in digital trade to protect African domestic industries and platforms - Rotich, Nelly Chepngetich (University of Pretoria, 2025)
As technology continues to advance, more trade is moving online. The increase in digital trade brings with it both opportunities and challenges in the international trade field. The increase in digital trade could for instance result in a spike in digital trade imports which may subsequently cause or threaten to cause serious injury to domestic industries and platforms dealing in like or directly substitutable digital data/content and services. This would necessitate the application of safeguard measures to avert any such serious injury or threat to serious injury caused to the domestic industries and platforms. The procedure for applying safeguard measures to digital trade currently is unclear. The current legal framework on safeguard measures does not apply to digital trade despite increased digital trade over the years. Thus, this study explores the prospects and practical challenges relating to safeguard measures’ application to digital trade with a specific focus on African domestic industries and platforms. While domestic industries and platforms in any part of the world could be affected by surges in digital trade imports, Africa is in a precarious position. Intra-Africa digital trade volumes could be increased and disadvantages of African domestic industries and platforms by surges in digital trade imports could be prevented through regulation and judicious use of safeguard measures. This study established the need to regulate to tap into the potential of digital trade and prevent African industries and platforms from falling behind and from the disadvantage of market dominance by big techs from outside Africa. In conclusion, the study noted legal and institutional gaps in the application of safeguard measures to digital trade. The study has recommended that specific institutions at the global, continental and national levels take necessary actions to build a clear and robust framework for safeguard measures in digital trade.
Keywords: Digital trade; International Trade